Off‐great‐circle paths in transequatorial propagation: 2. Nonmagnetic‐field‐aligned reflections. Issue 11 (5th November 2016) - Tsunoda, Roland T.; Maruyama, Takashi; Tsugawa, Takuya; Yokoyama, Tatsuhiro; Ishii, Mamoru; Nguyen, Trang T.; Ogawa, Tadahiko; Nishioka, Michi
Abstract: There is considerable evidence that plasma structure in nighttime equatorial F layer develops from large‐scale wave structure (LSWS) in bottomside F layer. However, crucial details of how this process proceeds, from LSWS to equatorial plasma bubbles (EPBs), remain to be sorted out. A major obstacle to success is the paucity of measurements that provide a space‐time description of the bottomside F layer over a broad geographical region. The transequatorial propagation (TEP) experiment is one of few methods that can do so. New findings using a TEP experiment, between Shepparton (SHP), Australia, and Oarai (ORI), Japan, are presented in two companion papers. In Paper 1 (P1), (1) off‐great‐circle (OGC) paths are described in terms of discrete and diffuse types, (2) descriptions of OGC paths are generalized from a single‐reflection to a multiple‐reflection process, and (3) discrete type is shown to be associated with an unstructured but distorted upwelling, whereas the diffuse type is shown to be associated with EPBs. In Paper 2 (P2), attention is placed on differences in east‐west (EW) asymmetry, found between OGC paths from the SHP‐ORI experiment and those from another near‐identical TEP experiment. Differences are reconciled by allowing three distinct sources for the EW asymmetries: (1) reflection properties within an upwelling (see P1), (2) OGC paths that depend on magnetic declination of geomagnetic field ( B ), and (3) OGC paths supported by non‐ B ‐aligned reflectors at latitudes where inclination of B is finite. Key Points: Two sources of east‐west asymmetry, one in plasma structure, other in experiment configuration Diffuse scatter in forbidden region is indicative of an unidentified reflection source Conclusion: nonmagnetic‐field‐aligned reflectors are present away from dip equator